Improving the safety of railway transport by changing the system of examining and monitoring drivers - Przemysław Brona; Adam Dąbrowski; Beata Piwowar (Przegląd Komunikacyjny)
Abstract: The article presents the most important aspects of changes in the training and examination system for candidates for train drivers and train drivers, which will enter into force on January 1, 2023. First, the system currently in force in Poland is characterized and its basic disadvantages are indicated. Then, the scope of legal changes resulting from the amendment to the Act on Rail Transport is described, which will lead to the separation of training and examination processes, and, as a result, to improvement of the efficiency of these processes. The article also presents the scope of activities of the currently built Center for Examination and Monitoring of Train Drivers, which will function at The Office of Rail Transport and will be equipped with modern simulators. Keywords: Train driver; Training; Examination; Simulator